Radical Cyclopropanol Ring Opening Initiated Tandem Cyclizations for Efficient Synthesis of Phenanthridines and Oxindoles - Davis, Dexter C.; Haskins, Christopher W.; Dai, Mingji (Synlett, 2017)
β-Keto radicals can be readily generated from single-electron oxidation and ring opening of cyclopropanols. Herein, we report new ways of trapping β-keto radicals derived from Mn(III)-mediated oxidative cyclopropanol ring opening with biaryl isonitriles and N-aryl acrylamides derived from anilines. Through tandem radical cyclization processes, substituted phenanthridines and oxindoles can be synthesized in one step and good to excellent yield. These new synthetic methods feature broad substrate scope and mild reaction conditions, efficiently form two carbon–carbon bonds, and use cheap and commercially available manganese salts as oxidants. Concomitant installation of ketone functionality in the final products provides a handle for further functionalization of these important and biologically relevant scaffolds.
Keywords: cyclopropanol; radical; phenanthridine; oxindole; manganese